2018
DOI: 10.1111/inr.12452
|View full text |Cite
|
Sign up to set email alerts
|

Perceived benefits and barriers of implementing nursing residency programs in Jordan

Abstract: Policy makers, nurse educators, and nurse administrators and clinical nurses need to collaborate to develop a formal system with binding policies and regulations concerning the implementation of Nursing Residency Program. There is also a need to address and modify current orientation programmes offered by hospitals for novice nurses to enhance their transition into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The incongruency between education and practice was believed to often lead to a reality shock in the practice environment. (23)The sources reviewed suggested that new health professionals experienced high levels of tension, coupled with anxiety and nervousness upon entering the world of practice (6,7,20,(25)(26)(27)29,32,33). O'shea et al (22) emphasized that the 'reality shock' and anxiety among new health professionals was intense, particularly in the rst ve months of transition into practice.…”
Section: Theme 3: Professional Competencesmentioning
confidence: 99%
See 4 more Smart Citations
“…The incongruency between education and practice was believed to often lead to a reality shock in the practice environment. (23)The sources reviewed suggested that new health professionals experienced high levels of tension, coupled with anxiety and nervousness upon entering the world of practice (6,7,20,(25)(26)(27)29,32,33). O'shea et al (22) emphasized that the 'reality shock' and anxiety among new health professionals was intense, particularly in the rst ve months of transition into practice.…”
Section: Theme 3: Professional Competencesmentioning
confidence: 99%
“…They experienced varying levels of stress beyond their expectations which impacted their transition (3,6,13,20,21,25,26,(30)(31)(32)(33). New health professionals often felt incapable of managing stressful emotional work-related situations such as death and dying (13,20,23).…”
Section: Theme 3: Professional Competencesmentioning
confidence: 99%
See 3 more Smart Citations